Linking environmental and innovation policy - Reyer Gerlagh; Snorre Kverndokk; Knut Einar Rosendahl (University of Oslo, Department of Economics, 2008)
This paper addresses the timing and interdependence between innovation and environmental policy in a model of research and development (R&D). On a first-best path the environmental tax is set at the Pigouvian level, independent of innovation policy. With infinite patent lifetime, the R&D subsidy should be constant and independent of the state of the environment. However, with finite patent lifetime, optimal innovation policy depends on the stage of the environmental problem. In the early stages of an environmental problem, abatement research should be subsidized at a high level and this subsidy should fall monotonically over time to stimulate initial R&D investments. Alternatively, with a constant R&D subsidy, patents' length should initially have a very long life-time but this should be gradually shortened. In a second-best situation with no deployment subsidy for abatement equipment, we find that the environmental tax should be high compared to the Pigouvian levels when an abatement industry is developing, but the relative difference falls over time. That is, environmental policies will be accelerated compared to first-best.
Keywords: H21; O30; Q42; 330; Environmental policy; research and development; innovation subsidies; patents; Umweltpolitik; Ökosteuer; Forschungssubvention; Patent; Internalisierung externer Effekte; Second Best; Theorie